The Importance of Platelets in the Expression of Monocyte Tissue Factor Antigen Measured by a New Whole Blood Flow Cytometric Assay - Amirkhosravi, A; Alexander, M; May, K; Francis, D A; Warnes, G; Biggerstaff, J; Francis, J L (Thrombosis and Haemostasis, 1996)
Previous methods for the determination of monocyte tissue factor (TF) have been technically complex, difficult to standardize, prone to spuriously elevated results and difficult to implement in a clinical laboratory environment. We report the development of a two-color whole blood cytometric technique that overcomes many of these disadvantages. The assay uses small volumes of citrated blood (1.0 ml), can be performed in under one hour (if endotoxin stimulation is not performed), is reproducible (CV = 5%) and uses methodology commonly available in clinical laboratories. Baseline (mean ± SD) expression of monocyte TF in normal subjects was very low (1.1 ± 0.95%, Mean Fluorescence [Mean FL] 0.20 ± 0.01) making relatively small increases easy to detect. Monocyte TF expression following endotoxin (LPS) stimulation for 1 h was 34.6 ± 11.2% (Mean FL 0.32 ± 0.04). LPS-stimulated activity varied between subjects (21-68%) but was remarkably consistent for individual subjects (CV = 5.4%). Stimulated monocyte TF expression was directly proportional to the platelet count and was reduced by platelet protective anticoagulants and by ingestion of aspirin. Non LPS-stimulated monocyte TF was markedly increased, in a dose-dependent manner, by adding collagen to whole blood. This was apparently associated with platelet-monocyte binding and could be abolished by anti-P-Selectin. We conclude that the whole blood flow cytometric assay of monocyte TF may be a valuable tool for clinical use and a useful model system for evaluating the humoral and cellular factors governing monocyte TF expression in a natural environment.